Learning Strategy: The Utilization of AI as a Learning Tool for PAI Students in the Digital Era - Nasution, Abdul Fattah (LPPM Universitas Ibn Khaldun, Bogor, 2025)
The digital era has transformed the conventional learning paradigm towards technology-based learning, especially with the emergence of Artificial Intelligence (AI) that offers the potential for learning personalization. In the context of Islamic Religious Education (PAI), AI integration faces specific challenges related to the validity of religious content and the maintenance of the spiritual dimension. This research aims to analyze the strategy of using AI as a means of learning for PAI students in the digital era, identify the potential and challenges of its implementation, and develop a learning model that is in line with Islamic values. The research uses a Mixed Method with a Sequential Exploratory Design approach. Qualitative data was collected through in-depth interviews with PAI students, classroom observations, and documentation. Quantitative data was obtained through a structured survey of 72 respondents of PAI students using Google Form. The findings show a gap in learning quality where only 30-40% of lecturers apply optimal learning strategies. PAI students showed a high acceptance of AI with 71% using it for reference search, 61% finding it helpful in understanding difficult concepts, and 52% using it for material summaries. However, the impact on discussion confidence is still limited (38%) and its use in learning routines is situational (39% consistent), so the integration of AI in PAI learning has great potential to improve learning personalization and efficiency of access to Islamic knowledge resources, but requires a hybrid learning model that positions AI as a reinforcement of human teaching without replacing the essential role of lecturers in the transmission of values and spiritual guidance. The development of a phased implementation framework that includes standardization of learning quality, improved AI literacy, and ethical considerations that are in line with Islamic values is needed